Mechanical and Thermal Characteristics of Bio-Nanocomposites Consisting of Poly-L-lactic Acid and Self-Assembling Siloxane Nanoparticles with Three Phases - Masatoshi Iji; Naoki Morishita (Journal of Nanotechnology)
Biopolymer nanocomposites (bio-nanocomposite) consisting of poly-L-lactic acid (PLLA) and siloxane nanoparticles with three phases, a high-density siloxane phase (plural cores), an elastomeric silicone phase, and a caprolactone oligomer phase, were developed to increase the mechanical properties of PLLA. The nanoparticles, average size of 13 nm, were self-assembled by aggregation and condensation of an organosiloxane with three units: isocyanatepropyltrimethoxysilane (IPTS), polymethylpropyloxysiloxane (PMPS), and a caprolactone oligomer (CLO), which form each phase. The bio-nanocomposite was produced using PLLA and the nanoparticles. Bending and tensile testing showed that the use of these nanoparticles (5 wt% in PLLA) greatly increases the tenacity (breaking strain) of PLLA while maintaining its relatively high breaking (maximum) strength. The elongation of the nanocomposite was more than twice that of PLLA while the elasticity modulus and breaking (maximum) strength were comparable to those of PLLA. The nanoparticles also increased the impact strength of PLLA. The use of the nanoparticles almost did not show adverse affect on the thermal resistance of PLLA. The nanocomposite’s heat resistance indicated by the glass transition temperature and heat distortion temperature was fairly kept. The decomposition temperature of the nanocomposite somewhat increased.